Covid-19 and the Philosophy of Education: Recuperating Africa’s Triple Heritage - Charles Prempeh (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2023)
The Covid-19 pandemic mandated the closure of all schools globally. E-learning programmes were introduced to promote learning throughout the crisis. This paper, therefore, investigates the impact of Covid-19 e-learning and teaching on students’ social life, indexed by their practice of social conviviality after the pandemic. The study employed multiple sampling techniques in selecting students in the second cycle and tertiary institutions in Accra, Ghana for the study. Using data collected from extensive interviews with students, teachers/lecturers and parents, backed by personal observations, the study found out that the social skills of students were negatively impacted by the pandemic, as several students suffered multidimensionality of social exclusion when schools were re-opened after lockdown rules were liberalised. The e-learning approach that Ghana introduced to stem the debilitating impact of the pandemic yielded some positive results – helping the education sector to retain contact hours. Nevertheless, the outcome of the pandemic had some negative social consequences. Students were unable to effectively recuperate their social skills in fostering social conviviality. Considering the outcome of the study’s findings, the paper concludes that Ghana needs to invest in its Triple Heritage – through the synthesisation of human ontological dignity that is embedded in Islam, Christianity, and indigenous worldview – to restructure its educational curriculum as part of rejuvenating social conviviality among students. The paper contributes to knowledge by providing evidence of the social impact of the pandemic. However, it also recommends a need for further research to explore how Ghana can broaden the frontiers of its heritage without provincializing or marginalisation emerging minority cultures.